2007
DOI: 10.1007/s00508-007-0825-0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of columnar-lined esophagus in patients with gastroesophageal reflux disease

Abstract: Columnar-lined esophagus cannot be excluded by endoscopy. In patients with gastroesophageal reflux disease, biopsy sampling of normal-appearing junction is recommended for histopathologic exclusion of intestinal metaplasia and low-grade dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Endoscopic equipment: Esophagogastroduodenoscopy was performed using an Olympus endoscope GIF6 connected to an Olympus video unit (CV-200, CLV-u20, TC-V1, EXERA CV-160; Olympus Inc. Austria) connected to a Sony monitor system (Sony Company Austria), as previously described [30,31]. Biopsies were obtained using Olympus biopsy forceps FB-24 KR-1 (Olympus Inc. Austria) [30,31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic equipment: Esophagogastroduodenoscopy was performed using an Olympus endoscope GIF6 connected to an Olympus video unit (CV-200, CLV-u20, TC-V1, EXERA CV-160; Olympus Inc. Austria) connected to a Sony monitor system (Sony Company Austria), as previously described [30,31]. Biopsies were obtained using Olympus biopsy forceps FB-24 KR-1 (Olympus Inc. Austria) [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…We recently found that all of 114 persons with gastroesophageal reflux disease (GERD) had cardiac or oxyntocardiac mucosa at the endoscopic esophagogastric junction, i.e. the level of the rise of gastric folds [30]. In none of the patients, even in those with an endoscopically normal-appearing esophagogastric junction, did biopsies contain gastric oxyntic mucosa.…”
mentioning
confidence: 98%
“…Whenever neoplastic consequences of GERD are discussed, a recurrent exposition of the esophagus to refluxate will lead GERD potentially to progress into metaplasia and dysplasia [4]. However, the dissection of the distal esophagus during surgery might lead to an altered sensitivity within the esophagus, thus leading to esophagitis without heartburn when reflux recurs.…”
Section: Dear Sirsmentioning
confidence: 99%
“…Viral infections, inflammation, autoimmune processes and a genetic predisposition are discussed as possible causes. The condition begins with slight swallowing disturbances and progresses slowly over years; if untreated it often results in a dilated aperistaltic (sigmoid or mega-) esophagus at risk for aspiration, malignoma [1][2][3][4] or even perforation. The main symptoms are dysphagia for liquid and solid food, regurgitation of indigested food, and heartburn.…”
Section: Introductionmentioning
confidence: 99%